(untitled) (Journal of Pharma Insights and Research, 2026)
Scrotal hypospadias is a severe phenotypic expression of male genitourinary malformation, characterized by a proximal urethral meatus, significant ventral chordee, and often a bifid scrotum. Successful management remains a surgical challenge, necessitating a balance between functional patency and aesthetic restoration. A four-year-old male born with a penoscrotal urethral opening and marked penile curvature underwent a staged surgical strategy utilizing the Byar’s technique to address the complex anatomy systematically. The first stage focused on chordee correction, urethral plate mobilization, and initial neourethral construction using local tissue flaps, including a tunica albuginea flap for reinforcement. The second stage involved the completion of the neourethra and glanuloplasty to achieve a terminal meatus. Post-operative outcomes demonstrated successful wound healing and the restoration of a normal urinary stream without fistula formation or stricture. Staged repair continues to be a reliable approach for proximal hypospadias, providing the necessary tissue handling and recovery time required to minimize long-term complications. This case shows the utility of the Byar’s procedure in achieving favorable outcomes in complex pediatric urological anomalies through individualized surgical planning